Potentiometric of bioethanol production from cantaloupe waste (Magassi Neishabouri Cultivar) - Rouhollah Salehi; Ahmad Taghizadeh-Alisaraei; Fakhri Shahidi; Ahmad Jahanbakhshi (Journal of the Saudi Society of Agricultural Sciences)
The ever-increasing need of the human beings to energy has brought about concerns regarding the decrease in the amount of energy resources. So, renewable energies have become very important and have obtained a special status in today's world. Using bioethanol as a renewable resource to be blended with other fuels in internal combustion engines has attracted many researchers to itself. Thus, in this study, we assess the amount of bioethanol extracted from cantaloupe waste (Magassi Neishabouri Cultivar) to be used as a fuel. To do so, considering the 15 kg capacity of the device's fermenter, 12 kg of refined cantaloupe sugar syrup and three kilograms of water (with the standard ratio of 4 to 1), i.e. a total of 15 kg of substrate with the brix degree of 20, as well as 75 g of saccharomyces cerevisiae yeast, cultured in standard conditions (5 g of yeast for each kilogram of substrate) were transferred into the fermenter. The tests were conducted in 35 h with three replications and at three different rotation speeds of the fermenter's mixer. Sampling took place every five hours. Fermentation temperature was set as 30 °C and distillation temperature was set to be 78.5 °C which is the standard temperature of bioethanol's boiling point. The results showed that about 49.5 g of bioethanol were extracted from each kilogram of cantaloupe syrup. In comparison to the results obtained by other researchers, it became clear that due to its high sugar level, cantaloupe waste is one of the appropriate options for the production of bioethanol. In addition, considering the rate of the alcohol produced and in order to optimize energy consumption, it was seen that the best speed for the fermenter's mixer, was 120 rpm. Keywords: Bioethanol, Renewable energy, Cantaloupe waste